What is the gender representation in authorship in later phase systemic clinical trials in biliary tract cancer (BTC)? - a retrospective review of the published literature. Issue 10 (26th October 2022) - McNamara, Mairéad G; Bridgewater, John; Goyal, Lipika; Jacobs, Timothy; Wagner, Anna D; Goldstein, David; Shroff, Rachna; Moehler, Markus; Lowery, Maeve; Bekaii-Saab, Tanios; Kelley, Robin K; Furuse, Junji; et al.
Abstract : Objectives: Female physicians in medicine are increasing, but disparities in female authorship exist. The aim of this study was to characterise factors associated with female first (FF) and female senior (SF) authorship in later phase systemic oncological clinical trials in biliary tract cancer (BTC) and identify any changes over time. Setting: Embase/Medline identified trial publications in BTC (2000–2020) were included. χ 2 tests and log regression were used (assessed factors associated with FF and SF authorship, including changes over time (STATA V.16)). Primary outcome measure: FF and SF authorship in later phase systemic oncological clinical trials in BTC. Secondary outcome measure: Any changes over time? Results: Of 501 publications, 163 met inclusion criteria. The median percentage of female author representation in publications was 25%; there were no female authors in 13% of publications. Geographic location of the home institution of the first and senior authors was Asia (42%/42%), Europe (29%/29%), USA (24%/22%) and other (4%/6%), respectively. Overall, FF and SF author representation was 20% and 10%, respectively. The median position of the first female author was second in all the publication author lists. The phase of trial, journal-impact factor, industry funding or whether the study met its primary endpoint did not impact FF/SF author representation. More SF authors had home institutions in 'other' geographic locations (40% in 10 trials) (p=0.02) versus Asia (6%), Europe (8%) and USA (14%). There were no significant changes in FF/SF representation over time (p=0.61 and p=0.33 respectively). Conclusions: FF and SF author representation in later phase systemic clinical trial publications in BTC is low and has not changed significantly over time. The underlying reasons for this imbalance need to be better understood and addressed.